2023
DOI: 10.1590/s1677-5538.ibju.2023.0053
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perioperative pelvic floor muscle exercise on urinary incontinence after radical prostatectomy: a meta-analysis

Abstract: Background: Pelvic floor muscle exercise (PFME) is the most common conservative management for urinary incontinence (UI) after radical prostatectomy (RP). We performed this meta-analysis to investigate whether PFME during the entire perioperative period, including before and after RP, can significantly improve the recovery of postoperative UI. Methods: We systematically reviewed randomized controlled trials (RCT) from PubMed, Medline, web of science, Cochrane library, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Dr. Geng and collegues from China performed on page 441 ( 6 ) a nice metanalysis about the effect of perioperative pelvic floor muscle exercise on urinary incontinence after radical prostatectomy and concluded that the application of Pelvic floor muscle exercise (PFME) after radical prostatectomy significantly reduced the incidence of early post operative urinary incontinence (UI) and additional preoperatively PFME had no significant improvement on the recovery of UI.…”
mentioning
confidence: 99%
“…Dr. Geng and collegues from China performed on page 441 ( 6 ) a nice metanalysis about the effect of perioperative pelvic floor muscle exercise on urinary incontinence after radical prostatectomy and concluded that the application of Pelvic floor muscle exercise (PFME) after radical prostatectomy significantly reduced the incidence of early post operative urinary incontinence (UI) and additional preoperatively PFME had no significant improvement on the recovery of UI.…”
mentioning
confidence: 99%